El desempe\~no exportador en las pymes manufactureras a través de un modelo estructural basado en intangibles - Francisco Villena Manzanares (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2016)
– This research tested and empirically analyzes the in uence of certain intangibles business on the export performance of manufacturing SMEs. Specifically, the proposed research model assesses the relationship between participative management, entrepreneurial culture and innovative orientation, managerial capacity and export performance. Considering the innovative orientation as a key in these businesses to compete in foreign markets, and export performance as a measure of competitive success, elaborate on how it affects promote an entrepreneurial culture, and how it in uences managerial capacity to conquer external markets. The technique Partial Least Squares (PLS) has been applied in 180 manufacturing SMEs. The results show that the entrepreneurial culture is a mediating variable between participatory management style and innovative orientation of the company and managerial capacity affect export performance but not moderate the relationship between innovation and export performance orientation.
Keywords: L21; M14; M3; 330; entrepreneurial culture; export performance; innovative orientation; participative management; managerial ability